INOS-selective inhibitors for cancer prevention: promise and progress. (November 2012) - Janakiram, Naveena B; Rao, Chinthalapally V
Nitric oxide (NO) is involved in various physiological functions and its role in tumorigenesis has been well studied. A large majority of human and experimental tumors appear to progress owing to NO resulting from iNOS, further stimulated by proinflammatory cytokines. Conversely, in some cases, NO is associated with induction of apoptosis and tumor regression. This dichotomy of NO is largely explained by the complexity of signaling pathways in tumor cells, which respond to NO very differently depending on its concentration. In addition, NO alters many signaling pathways through chemical modifications, such as the addition of S- nitrosothiols and nitrosotyrosine to target proteins altering various biological pathways. Hence, iNOS inhibitors are designed and developed to inhibit various organ site cancers including the colon. Here, we review iNOS expression, generation of NO, involvement of NO in altering signaling pathways, and iNOS select inhibitors and their possible use for the prevention and treatment of various cancers.